The Japanese discovery of Europe : - Keene, Donald (Routledge and K. Paul, 1952)
Keene provides a fascinating account of Japanese views of what Europe might be like based on emerging understanding of European knowledge and technology. Before American gunships forced Japan open and the Meiji "restoration" embarked on a program of rapid industrialization (and militarization), there was a base of thought on trying to adapt what seemed useful from the west in ways compatible with Japanese conceptions of the essence of Japaneseness. Keene's classic book provides valuable background to understanding the rapid "modernization" and militarism of the late-19th-century (with successful wars with first China, then with Russia just before and just after the turn of the 20th century).